Assisting in Long-Term Care, 7th Edition - Leann Miller; Mary Jo Mirlenbrink Gerlach (Cengage Learning, 2019)
ASSISTING IN LONG-TERM CARE, 7th Edition is the perennial choice among top Certified Nursing Assistant programs. This user-friendly, all-in-one resource delivers skills and confidence to help students compete for top jobs in long-term care and sub-acute hospital settings. Helpful discussions include professional communication, roles and responsibilities, job search, and an overview of care settings. And, to prepare students for CNA certification exams, this resource addresses daily clinical processes, residents' rights, nutrition and hydration, restorative care, resident mobility, and patient safety-all according to federal OBRA standards for nursing home care. ASSISTING IN LONG-TERM CARE is available in hardcopy and eBook formats, includes supportive study features, and offers a full suite of online learning and course preparation tools.